1D Copper-based nanowire decorated with trimetallic nanoparticles affording abundant edges toward hydrogen generation in wide pH range. (1st June 2023) - Du, Yingxue; Chen, Zhi; Gong, Yuecheng; Li, Qichang; Xiao, Weiping; Xu, Guangrui; Li, Bin; Wang, Xinping; Wu, Zexing; Wang, Lei
Graphical abstract: The synthesized Cu-Ru-PBA-H2 /Ar electrocatalytic materials have excellent electrocatalytic performance for HER, with low overpotentials of 37, 34 and 89 mV, driving 10 mA cm −2 in alkaline, acidic and neutral media, respectively. The Cu-PBA-H2 /Ar synthesized without Ru has excellent OER performance, with a potential of only 1.48V at a current density of 10 mA cm −2, and the electrolytic cell composed of the above materials can be powered by sustainable energy. Highlights: One-dimensional (1D) copper nanowires decorated with trimetallic nanoparticles are developed via etching and coordination engineering. The self-supported Cu-Ru-PBA-H2 /Ar exhibit excellent electrocatalytic performance and long-term stability for HER. The synthesized electrocatalyst exhibits abundant pyridinic N to boost the catalytic activity. Abstract: It still faces significant challenges in exploiting highly efficient and low-cost electrocatalysts for oxygen evolution reactions (OER) and hydrogen evolution reactions (HER) to boost the development of hydrogen energy. Herein, one-dimensional (1D) copper-based nanowires decorated with trimetallic nanoparticles on copper foam by in situ etching, forming PBA analogue and following low-temperature pyrolysis approach (Cu-Ru-PBA-H2 /Ar). The specific 1D nanostructure decorated with numerous trimetallic nanoparticles can provide abundant active sites and favors mass transport during the electrocatalytic process. Moreover, the introduced Ru species and PBA analogue play pivotal roles in promoting catalytic performance. Then, the designed Cu-Ru-PBA-H2 /Ar shows excellent all-pH HER performance with small overpotentials of 37, 34, and 89 mV in basic, neutral and acidic media, respectively, for providing 10 mA cm −2 . This work provides a valuable way to exploit novel catalysts with hierarchical nanostructure in energy-related applications.